The Five Major Personality Factors and its Relationship to Career Decision-Making Among Jordanian University Students - Habi, Sarah Hosny; Shawareb, Iyad Graes (Journal of Educational and Psychological Sciences, 2021)
The aim of this study was to identify the major five personality factors and their relationship with career decision-making among university students.The study sample consisted of (371) male and female students from two universities, the University of Islamic Sciences and the University of Petra during the first semester (2020/2021). They were selected by the available research methods.To achieve the objectives of this study, two main scales were used:The scale of the five major personality factors The Major, which consisted of (48) characteristics.The measurement of career decision-making, which consisted of (38) characteristics which were applied to the university students.Methods: After analyzing their validity, the second was applied to the study sample and the relational descriptive approach was used.The results of the study showed the existence of a statistically significant correlation between the desired strategy and the neurotic factor and the presence of a statistically significant positive correlation between the desired strategy and all the remaining personality factors.The results also showed the existence of a statistically significant positive correlation at the level between the safe strategy and four personality factors except for the neurotic factor.The results showed the nonexistence of a statistically significant correlation at the level between the composite strategy and personality factors in light of the study results.Conclusion: In light of the results showed earlier, it is recommended to conduct more surveys, qualitative and experimental studies related to the five major personality factors and professional decision-making on other groups.
Keywords: The Major Five Personality Factors; Career Decision Making; University Students